2022
DOI: 10.1111/1756-185x.14279
|View full text |Cite
|
Sign up to set email alerts
|

Early experience of COVID‐19 vaccine‐related adverse events among adolescents and young adults with rheumatic diseases: A single‐center study

Abstract: Objective Considering the concerns regarding the coronavirus disease‐2019 (COVID‐19) vaccine safety among pediatric patients with inflammatory rheumatic diseases (IRD) due to a lack of data, an urgent need for studies evaluating safety profiles of vaccines emerged. Methods Among participants vaccinated by CoronaVac inactive SARS‐CoV‐2 or BNT162b2 messenger RNA (mRNA) COVID‐19 (Pfizer‐BioNTech) vaccine, healthy children under 18 and patients under 21 with an at least 1‐year follow‐up period in our department fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 30 publications
6
46
0
Order By: Relevance
“…However, those who were using IL-1 were more inclined to have post-vaccine flare than those who were not, suggesting a relation between disease severity and exacerbation. In line with our findings, a very recent study done among young adults with diverse RD found that 15 of 123 patients with FMF had typical peritonitis attack after mRNA vaccine [ 43 ]. Another recent survey done in 175 patients with autoinflammatory diseases reported that single dose of COVID-19 vaccine was generally well tolerated with no serious outcome and about 20% AEs were consistent with a flare of the underlying disease [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, those who were using IL-1 were more inclined to have post-vaccine flare than those who were not, suggesting a relation between disease severity and exacerbation. In line with our findings, a very recent study done among young adults with diverse RD found that 15 of 123 patients with FMF had typical peritonitis attack after mRNA vaccine [ 43 ]. Another recent survey done in 175 patients with autoinflammatory diseases reported that single dose of COVID-19 vaccine was generally well tolerated with no serious outcome and about 20% AEs were consistent with a flare of the underlying disease [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…Multiple studies evaluating various COVID-19 vaccines have reported safety of these in adolescent and adult patients with SLE [ 40 42 ]. An online survey in Denmark explored the safety of BNT162b2 (Pfizer/BioNTech) vaccine and compared it to the original vaccine trial in patients with SLE ( n = 182) and rheumatoid arthritis (RA) ( n = 103).…”
Section: Covid-19 Vaccination In Slementioning
confidence: 99%
“…In a single-center study evaluating the safety of COVID-19 vaccination in pediatric SLE, adverse events were noted in 4 of 16 patients (25%), and none were severe [ 40 ]. The adverse events were more frequent with the BNT162b2/Pfizer BioNTech vaccine than CoronaVac inactivated SARS-CoV-2.…”
Section: Covid-19 Vaccination In Slementioning
confidence: 99%
See 1 more Smart Citation
“…Coronavirus disease 2019 (Covid-19) is an infectious disease spread by a novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [ 1 ]. This pandemic has affected millions of people around the world in the last two years.…”
Section: Introductionmentioning
confidence: 99%